Adaptive Clinical Trials: Overview of Early-Phase Designs and Challenges. (January 2014) - Marchenko, Olga; Fedorov, Valerii; Lee, J. Jack; Nolan, Christy; Pinheiro, José
In this paper, the authors describe developments in adaptive design methodology and discuss implementation strategies and operational challenges in early-phase adaptive clinical trials. The BATTLE trial—the first completed biomarker-based Bayesian adaptive randomized study in lung cancer—is presented as a case study to illustrate main ideas and share learnings.